Agents of meta: Institutional actors in the journalism space and the innovation of local news. (June 2023) - Lowrey, Wilson; Deavours, Danielle; Singleton, William
This study sheds light on the increasingly important roles that meta-level organizations, a type of institutional actor, play in the processes of local journalism innovation. Examples of meta-level organizations in journalism include journalism professional associations, training and research centers, nonprofits, and trade publications. Definitionally, metalevel organizations embrace the functions of coordination, regulation, agenda-setting, information diffusion, and the boundary negotiation of an institutionalized space. This qualitative study uses in-depth interviews to explore the roles of meta-level organizations in relation to the troubles of local journalism, how these roles are enacted at professional association conferences, and how they are conceptualized by journalists and representatives of meta-level organizations. We found evidence of three traditional roles of meta-level organizations – information, interaction, existential roles – across different types of meta-level organizations. Respondents tended to view these roles through a lens of resource scarcity. We also found evidence of the role of self-maintenance —i.e., meta-level organizations have their own institutional spaces and an interest in self-preservation—as well as the role of conceptualization or theorization, of innovations, and an emergent role of translation . Translation involves adaptation of abstract ideas to local-level sites, as well as communication of results from local-level experimentation back to the field level, an increasingly important role in a resource-poor local journalism space that is inundated with a flood of new field-level initiatives.